Back-office service work: bureaucracy challenged? - Korczynski, Marek (Work, employment and society, 2004)
Much of the current literature on service work has focused on front-line, customer-facing jobs. Research and theory suggest that while the way in which this work is organized is to a significant degree underpinned by rationalization, there is also an important customer-oriented strand in the organization of front-line work. This begs the question of how work is organized in back-office service work, i.e. service jobs involving work with and for the front-line staff but in which there is no direct interface with customers. Are these jobs also organized as a 'customer-oriented bureaucracy' or are they subject to more straightforward bureaucratization? This article reports on case studies of two types of back-office work — staff in the back office to a call centre in an insurance firm, and staff in the back office to a mobile sales force in two financial service firms. The organization of work is examined systematically across the dimensions of work tasks, form of control, affect in relation to the customer and lateral relations with the front-line staff. It is concluded that to a significant degree back-office work in the three firms is organized according to bureaucratic principles. The conclusion argues that these results are likely to be typical for much of back-office service work.